The rumen microbiome: a crucial consideration when optimising milk and meat production and nitrogen utilisation efficiency - Matthews, Chloe (Gut Microbes, 2018)
Methane is generated in the foregut of all ruminant animals by the microorganisms present. Dietary manipulation is regarded as the most effective and most convenient way to reduce methane emissions (and in turn energy loss in the animal) and increase nitrogen utilization efficiency. This review examines the impact of diet on bovine rumen function and outlines what is known about the rumen microbiome. Our understanding of this area has increased significantly in recent years due to the application of omics technologies to determine microbial composition and functionality patterns in the rumen. This information can be combined with data on nutrition, rumen physiology, nitrogen excretion and/or methane emission to provide comprehensive insights into the relationship between rumen microbial activity, nitrogen utilisation efficiency and methane emission, with an ultimate view to the development of new and improved intervention strategies.